AN ANALYSIS OF TEACHER PEDAGOGICAL COMPETENCE IN TEACHING ENGLISH FOR SENIOR HIGH SCHOOL LEARNERS (VISION, 2022)
This research is motivated by the results of observations in the field, most teachers are still less effective in the learning process. Teachers are still lacking in assessing and evaluating learning. So in this study the researchers focused on pedagogic competence, because basically pedagogic competence is one of the important competencies that must be possessed by a teacher in teaching and learning activities.This study aims to determine the pedagogic competence of teachers at SMA N2 SEI KANAN. The research method used is descriptive qualitative research method. The research subjects who were used as research informants were English teachers. Data collection techniques in this study were observation, interviews and documentation. This study uses three instruments, namely observation sheets, interview sheets and documentation. The data analysis technique in this study uses the theory of Milles and Huberman which includes three stages, namely data reduction, data display and conclusion drawing. This study uses a credibility test to test the validity of the data.The researcher's findings show that pedagogic competence is in the "pretty good" category, including the ability to master student characteristics, curriculum development competence, and communication competence. Competence in comprehending learning theory and teaching principles of learning, competency in educating learning activities, competence in developing student potential, and competence in assessment and evaluation are among the pedagogic competencies in the bad group. As a result, it can be inferred that instructors' pedagogic competency at SMA N2 SEI KANAN is still lacking.